Clinical effectiveness of Bacillus clausii and Lactic acid bacillus in acute diarrhea - Shah, Apurva C; Goyal, Dileep Kumar; Sareen, Devendra (Indian Journal of Child Health, 2020)
Background: Depending on the duration, acute diarrhea is defined as the passage of three or more loose or liquid stools per day lasting for 0.05). Conclusion: Both probiotic preparations were almost equally effective in achieving normal stool consistency and frequency in patients with acute diarrhea.